Data aesthetics - between clouds of information and subjective experience - Bjoernsten, Thomas (MedieKultur: Journal of media and communication research, 2016)
This article takes it point of departure from a three-year research project entitled “Making sense of data – understanding digital reality through contemporary artistic practices of visualization and sonification”. As the project does, so will this article focus on the analysis of specific practices and artefacts, occupied with exploring digital formats and data through both visualization and sonification strategies (the latter referring to the task of turning data into audible sound), thus, expanding the use of large data sets into the sphere of art and the aesthetic. The article will critically discuss such artistic renderings of what might be termed as ‘Big Data’ and how these various data-translations are presented in the form of artefacts, installations, and performances that establish different aesthetic experiences and effects. A further point developed within the article will be how the examples addressed here diverge according to the data sets used, as something either drawn from large public and (mostly) accessible databases or individually collected data.